Optimization and Implementation of Fed-Batch Strategy to Produce Ligninolytic Enzyme from the White-Rot Basidiomycete Pycnoporus sanguineus in Bubble Column Reactor - Evanildo F. de Souza; Isabella M. T. S. Santos; Felipe Souto; Verônica Calado; Nei Pereira (Fermentation, 2022)
The current work evaluates the production of ligninolytic enzyme optimization via response surface methodology using different inducers: acid cellulignin (CA); MnSO4 (Mn2+); CuSO4·5H2O (Cu2+); veratryl (3, 4-dimethoxybenzyl); alcohol (VA); Tween 80% (T80); and the carbon-to-nitrogen ratio (C/N). A further goal was implementing a fed-batch strategy to produce ligninolytic enzyme extracts from P. sanguineus 2512 using a bubble column reactor (BCR). The best optimized experimental condition in the shake flasks was a 7.5 C/N ratio, 0.025 g/L Cu2+, 1.5 mM Mn2+, 3.0 mM VA and 0.025 mM T80, resulting in 64,580, 9.10 and 80.72 U/L for Laccase (Lac), Manganese (MnP) and Lignin peroxidase (LiP) activities, respectively. In the BCR, three feedings were performed at 24 h intervals on the 6th, 7th and 8th days with a significant increase in Lac (99,600 U/L) and MnP (47.53 U/L) activities on the 8th day and a reduction on the 9th day of cultivation. The LiP activity peak was achieved on the 5th day (416 U/L) of cultivation, decreasing thereafter. Enzyme cocktails concentrated in hollow fiber in the third cultivation batch showed contents of 4 × 105 U/L, 220 U/L and 2.5 g/L for Lac, MnP and total proteins, respectively. The enzymatic cocktail with the highest LiP activity (1200 U/L) was obtained in the first batch. The results showed that the optimization of the biosynthesis of the ligninolytic enzymes provided satisfactory improvement in terms of Lac and MnP production per run.